Improvement of Ga distribution in Cu(In, Ga)(S, Se)2 film by pretreated Mo back contact. (1st March 2018) - Han, Anjun; Wang, Xian; Liu, Xiaohui; Huang, Yongliang; Meng, Fanying; Liu, Zhengxin
Graphical abstract: Highlights: The Mo back contacts were pre-sulfurized and selenized (PSS) before CIGSSe films deposition. Ga accumulation in CIGSSe film based on PSS Mo layer was weakened. Eg min in the space charge region and VOC of solar cell increased. The thermodynamic calculation confirms that the proposed hypothesis of bottom Se and S sources is effective. Abstract: In the two-step selenization process, Ga accumulation near back contact is a common problem, resulting in a lower band gap near front surface and then lower open circuit voltage (VOC ) of solar cell. In this work, Ga accumulation in Cu(In, Ga)(S, Se)2 (CIGSSe) film was weakened by pre-sulfurized and selenized (PSS) Mo back contacts. The sputtered dense Mo back contacts were sulfurized and selenized at different temperatures before Cu-In-Ga precursor deposition. Raman results show that MoS2, MoSe2 and pure Se phases were formed on the PSS Mo surface. These selenide and sulfide phases will become the bottom Se and S sources in the structure of PSS Mo/metal precursor during selenization process. The thermodynamic calculation confirms the bottom S and Se sources are effective. SIMS measurement shows the Ga back grading in CIGSSe films decreases when the PSS Mo back contacts are used. For higher substrate temperature (Tsub ) we find reduced steepness of the Ga back gradient. The S atomic percentage in CIGSSe is so small that the band gaps of CIGSSe are mainly determined by the Ga/(Ga + In) distribution. Therefore, the band gap in the space charge region (SCR) of solar cell increased when PSS Mo was used. As expected, VOC increased about 10 mV when TSub increased to 600 °C. Due to the enhancement of VOC and fill factor (FF), the conversion efficiencies (η) of solar cells was improved.